Quantum aspects of beam physics : (World Scientific, 2004)
This book will be a valuable source of reference to readers interested in the interdisciplinary frontiers of “quantum beam physics” that involve beam physics, particle physics, laser science, astrophysics, condensed matter physics, nuclear and atomic physics.The proceedings have been selected for coverage in: • Index to Scientific & Technical Proceedings® (ISTP® / ISI Proceedings)• Index to Scientific & Technical Proceedings (ISTP CDROM version / ISI Proceedings)• CC Proceedings — Engineering & Physical Sciences